Cultural Identity Transformation in Intercultural Marriage: An Ethnographic Study of Sundanese Women in France - Nyai Kartika; Prima Agustina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study investigates the cultural identity transformation of Sundanese women in intercultural marriages with French men living in France. Within the discipline of sociology and cultural studies, the research explores how these women negotiate the friction between Sundanese collectivist values and French individualism. Using a qualitative method and an ethnographic approach involving 15 participants married for at least five years, data were collected through in-depth interviews and field notes. The findings reveal that traditional Sundanese values, specifically the Pancawaluya philosophy (cageur, bageur, bener, pinter, singer), remain a central ethical foundation for the Sundanese women living in France. However, these values are dynamic; through Bourdieu’s concepts of habitus and hysteresis, the research shows that cultural displacement acts as a learning space rather than a failure of adaptation. The results highlight a significant transformation from a traditional